Serum Cortisol as an Early Biomarker of Cardiopulmonary Parameters Within the First 24 Hours After Aneurysmal Subarachnoid Hemorrhage in Intensive Care Unit Patients. (November 2020) - Bender, Michael; Stein, M.; Uhl, E.; Reinges, M. H. T.
Objective: Cardiopulmonary complications/stress are well-known phenomena in patients after aneurysmal subarachnoid hemorrhage (aSAH) and might be associated with an elevated serum troponin I (TNI) level. Since the glucocorticoid hormone cortisol is released during stress situations, the present study was conducted to investigate the influence of serum cortisol (SC) on cardiac and pulmonary parameters in patients after aSAH within the first 24 hours of intensive care unit (ICU) treatment. Patients and Methods: We retrospectively analyzed a cohort of 104 patients with aSAH admitted to our emergency department between January 2008 and April 2017. Blood samples were taken to determine SC and TNI. Demographics, initial Glasgow Coma Scale (GCS) score, World Federation of Neurosurgical Societies (WFNS) score, and Fisher grade were evaluated retrospectively. Mean norepinephrine application rate (NAR) in µg/kg/min and mean inspiratory oxygen fraction (OF) within the first 24 hours were defined as cardiopulmonary parameters. Results: An elevated SC value was found in 44 (42%) patients, and 27 (26%) patients showed an increased TNI value. In patients with initially increased SC value, a significant higher NAR ( P = .04) was needed. Furthermore, patients with initially elevated TNI value had a lower GCS score ( P = .0013) and a higher WFNS score ( P = .003) on admission and required a higher NAR ( P = .02) as well as OF ( P = .0008) within the first 24 hours of ICU treatment. Conclusions: In the current study, initially elevated SC values were associated with a higher need of NAR within the first 24 hours of ICU treatment after aSAH. Moreover, patients with initially elevated TNI values required an increased NAR and a higher OF so that these biomarkers could be useful to improve ICU treatment.